Interactive effect of temperature and CO2 increase in Arctic phytoplankton - Coello-Camba, Alexandra; Agustí, Susana; Holding, Johnna; Arrieta, Jesús M.; Duarte, Carlos M. (Frontiers in Marine Science, 2014)
An experiment was performed in order to analyze the effects of the increase in water temperature and CO2 partial pressure expected for the end of this century in a present phytoplankton community inhabiting the Arctic Ocean. We analyzed both factors acting independently and together, to test possible interactions between them. The arctic planktonic community was incubated under 6 different treatments combining three experimental temperatures (1 ºC, 6 ºC and 10 ºC) with two different CO2 levels of 380 ppm or 1000 ppm, at the UNIS installations in Longyearbyen (Svalbard), in summer 2010. Under warmer temperatures, a decrease in chlorophyll a concentration, biovolume and primary production was found, together with a shift in community structure towards a dominance of smaller cells (nano-sized). Effects of increased pCO2 were more modest, and although interactions were weak, our results suggest antagonistic interactive effects amongst increased temperature and CO2 levels, as elevated CO2 compensated partially the decrease in phytoplankton biomass induced by temperature in some groups. Interactions between the two stressors were generally weak, but elevated CO2 was observed to lead to a stepper decline in primary production with warming. Our results also suggest that future increases in water temperature and pCO2 would lead to a decrease in the community chl a concentration and biomass in the Arctic phytoplankton communities examined, leading to communities dominated by smaller nano-phytoplankton groups, with important consequences for the flow of carbon and food web dynamics.